DRIVING THE VILLAGE ECONOMY WITH SOCIALISATION AND MENTORING OF UMKM - Mahidin Fahmie; Rita Hayati; Al-Amin (Adiba Aisha Amira, 2024)
Improving the village economy through socialisation and mentoring of Micro, Small, and Medium Enterprises (MSMEs) is a strategic approach that has proven to be effective and sustainable. Hence, the importance of socialisation as a tool to provide an in-depth understanding of entrepreneurship to village communities. Through this comprehensive education, local communities can understand the benefits and techniques of starting and growing a business, which in turn, can improve their standard of living. More than just providing basic knowledge, socialisation fosters passion and confidence, which are often barriers to starting a business. Village MSME mentoring offers ongoing support in various aspects of business such as technical operations, management, marketing, and access to resources. With the right mentoring, village MSMEs can utilise technology, improve product quality, and implement effective marketing strategies. Mentors also assist in long-term business strategy planning, financial management, as well as building a wider market network including e-commerce. All of these contribute to improving the competitiveness of village MSMEs at the local, regional and national levels. In conclusion, socialisation and mentoring of MSMEs is a very effective instrument to drive the village economy. Proper education and ongoing support allow village MSMEs to thrive, thereby contributing significantly to the local economy. This not only improves individual welfare but also strengthens the village economy as a whole, making it more independent and resilient in the face of economic challenges. Investing in MSME socialisation and mentoring is a strategic move with positive long-term impacts, creating more prosperous and highly competitive villages.